Immune modulatory properties of nanoparticles on human dendritic cells - Al-Zahri, Reem (2018)
Dendritic cells (DCs) are professional antigen presenting cells that play a potent role as a key link between innate and adaptive immunity. Given the quintessential role of DCs in orchestrating immune responses, better understanding of conditions that control DC function could provide opportunities for developing new treatment strategies for infectious and autoimmune diseases. Recently, there is a growing interest to utilize nanoparticles (NPs) with diverse chemistry, size and other physicochemical attributes in vaccination, drug delivery systems, and diagnostics. There is emerging evidence for the effect of NPs size, shape, and other physiochemical properties on cellular responses; however, the impact of NPs on the immune system, and particularly the function and phenotype of DCs, is yet to be fully understood. The overall aim of this study was investigating the influence of different properties of NPs on DC phenotype, cytokine profile, function (e.g. endocytic ability) and metabolic profile. This was done by exposing DCs to a defined concentration of NPs, particularly, PLGA NPs, Silica (SNPs) and polystyrene (PS NPs), which were successfully fabricated or commercially sourced, respectively. The findings clearly demonstrated that particle size and the choice of material can affect different aspects of DC phenotype. While spherical Silica and PLGA NPs of 100 nm and 160 nm size range respectively do not change DC phenotype and function (endocytic ability), PS NPs of similar size and PLGA NPs of 500 nm size induce significant changes in DC phenotype and function. PS NPs of 150 nm and 200 nm size significantly suppress the expression of mannose receptor (MR or CD206) on DCs by around 90%-80% without affecting their viability, maturation status or cytokine profile. In addition, PLGA NPs of 500 nm size induced DC maturation as evidenced by high levels of CD83 expression.